Assessment of the Integration of Information and Communication Technology (ICT) in the Management of Human Resources in Universities in North West Zone, Nigeria - Umar, Abdulhakeem Sidi (Kashere Journal of Education, 2025)
This study examined the assessment of the integration of ICT in the management of human resources in universities in the Northwest Zone, Nigeria. The main objective was to ascertain the integration of ICT in the management of human resources in universities in the northwest zone, Nigeria. A convergent mixed method was used; the overall population of the study comprises 22,768 staff. Stratified sampling technique was used, Convenient and Purposive sampling techniques. 378 was used as the sample size for the quantitative method as identified by Research advisors (2006). The qualitative method, 72 respondents were sampled conveniently at a saturated level. Questionnaires and interview guides were used as instruments for data collection. The Questionnaire was Tagged “Questionnaire on the Integration of ICT in the Management of Human Resources in Universities in the Northwest Zone, Nigeria" (QIICTMRUNZN), was used. While interview guides were titled "In-depth Interview Guide on Integration of ICT in the Management of Human Resources in University" (IDIGIICTMRU). “Key Informant Interview Guide on Integration of ICT in the Management of Human Resources in University” (KIIIGIICTMRU) and “Focus Group Discussion Guide on Integration of ICT in Management of Human Resources in University” (FGDGIICTMRU). Null hypotheses were tested at the 0.05 level of significance, using ANOVA. The qualitative data was transcribed and analysed using NVIVO analytical software. Findings, among others, revealed that there was no Integration of ICT in Management of Human Resource in Universities. It was recommended that Universities implement ICT Integration in areas like recruitment, induction training, and virtual capacity-building training, among others.